Influence of drying on the biological potentials of Bixa orellana L. essential oil (Research, Society and Development, 2020)
The objective of this study was to evaluate the  influence of  drying temperature of Bixa  orellana  L leaves. the biological properties  of the essential oils (EOs)  obtained. The plant material a was  collected  and  submitted to a convectiva greenhouse of air at temperatures 35-55 °C. The EOs were obtained by hydrodistillation. The antimicrobial assay was performed using the Disk Diffusion Method against Staphylococcus aureus  and  Escherichia coli. For the biotoxicity assay, the lethality of the EOs in front of  Artemia salina was evaluated. Significant differences were observed in the properties of OE's. The temperature of 45 °C allowed to obtain the most efficient  bactericidal action against the microorganisms tested and the toxicity was also verified for the EO obtained at this temperature. This study concludes  through the analyzed activities that the drying temperature influences the properties  of  EOs and the temperature of 45° is stated as the most indicated for  B. orellana due to the better performance of the properties both in the antimicrobial assay and toxicity.